Problem uznania granic jako wyznacznik stosunków polsko-niemieckich = The problem of recognition of borders as a determinant of Polish-German relations - Nitschke, Bernadetta (1964- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
As a result of the end of WorldWar II, Poland was in the new geopolitical situation which conditioned the shape of state borders, i.e., territorial acquisitions in the West and losses in the East. The paper shows how it influenced Polish-German relations. Both Poland and Germany had to get used to the entirely new arrangement of political forces which was created in Europe. In 1949 two German states were formed. The People`s Republic of Poland (PRL) and Eastern Germany (GDR) found themselves under the influence of USSR. Therefore, it was necessary to regulate the relations between PRL and GDR first.
Keywords: pogranicze polsko-niemieckie; stosunki polsko-niemieckie; od 1945 r.